The Extreme Right, Climate Change and Terrorism - Macklin, Graham (Terrorism and political violence, 2022)
“Eco-fascism” has recently regained prominence following two of the most lethal extreme right terrorist attacks: the murderous assault on two mosques in Christchurch, New Zealand, which killed fifty-one, and the massacre at a Walmart in El Paso, Texas, which killed twenty-two. Both of these attacks were justified by their perpetrators, at least in part, in environmental terms. Brenton Tarrant, the Christchurch terrorist, went so far as to proclaim himself an “eco-fascist.” Whilst “radical right” populism is often associated with climate denial, “extreme right” environmentalism, with its roots in the “blood and soil” thinking of Nazism, is concerned with protecting the spiritual link that supposedly exists between man and nature. Having established the historical lineage of such ideas, the article explores how contemporary extreme right groups have reacted to population growth, migration, and climate change. It explores the emergence of a particular form of “dark green” environmentalism that builds upon the “blood and soil” ideas of Nazism, synthesizing them with an anti-human ecology derived from several sources including Greco-French Hitler-worshipper Savitri Devi; the “Unabomber” Ted Kaczynski; and the Finnish environmentalist and misanthrope Pentti Linkola. The misanthropic ideas of these three ideologues and their extreme “solutions” to environmental degradation and overpopulation represent an increasingly prevalent ideological tendency within extreme right subcultures online. The violent panaceas they advocate and envisage as being necessary to defend the natural environment will undoubtedly gain greater prominence as climate change-driven migration northwards to Europe intensifies.